Functions Commuting With an Arbitrary Fixed Bijection - Mach, Andrzej (Sarajevo Journal of Mathematics, 2024)
In this note a characterization of all bijective functions commuting with a fixed bijection φ:X → X, where X is an arbitrary nonempty set, is given. 2010 Mathematics Subject Classification. Primary 39B12; Secondary 26A18